The 1985 NAAAA Convention Nashville, Tennessee: A Review with Highlights and Business Minutes - (:unkn) unknown (My University, 1985)
These minutes reviewed the 10th annual N4A conference in January 1985, including executive board meetings. Topics included realigning regions, more time for region meetings at conferences, how toe journal would be organized, run, and costs.
Keywords: minutes